Testing of palm oil-based electric power transformer insulation oil as a renewable energy source - Hendri, Hendri; Arief, Yanuar Zulardiansyah; Syukur, Abdul (Universitas Negeri Padang, 2023)
Reducing petroleum resources and environmental problems, alternative insulating oils with biodegradable characteristics have become an alternative. Esterification of palm-based oil is expected to provide better and optimum electrical properties. The esterification of palm oil will be carried out as a test sample and observed for its electrical, physical and chemical properties such as PD characteristics, breakdown voltage, dissipation factor, viscosity, flash point, etc. The effect of thermal aging on oil samples will also be carried out to simulate real situations in power transformer applications. Then after obtaining the best formulation from the sample it will be used as insulating oil in electric power transformers (100kVA). The purpose of this research is to apply esterified palm oil as an electric power transformer oil. The method used in this research includes field research. Field research includes taking oil samples, measuring the breakdown voltage of transformer oil, and the color of transformer oil. The results obtained are insulating oil for electric power transformers based on palm oil. Palm oil has the advantage of being an environmentally friendly, biodegradable and renewable oil compared to the transformer oil used today which is based on petroleum. With the realization of transformer oil based on palm oil, it is hoped that it can provide great economic opportunities for Indonesia as one of the largest palm oil producers in the world and can also provide added value and increase the competitiveness of the palm oil industry in the future.